2021
DOI: 10.26710/jbsee.v7i1.1570
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus and Cognitive Dissonance, Behavior of Pakistanis During Pandemic Peak: A Study of Educated and Uneducated Citizens of Lahore

Abstract: This research aims to investigate the behavior of the citizenry residing in Provincial Capital of Pakistan’s largest populated province of Punjab. Based on quantitative approach, a questionnaire with closed ended questions was distributed between two divisions of society – educated and uneducated – to measure their behavior towards the pandemic. The researchers have made an attempt to measure the cognitive dissonance of the society towards COVID with this hypothetical assumption that uneducated people would bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Research shows that men and those who do not have health risk factors themselves or in their families, those with more education, and those from a higher socioeconomic position are less likely to follow recommended public health guidelines [11e13]. Furthermore, studies of health behaviors in Brazil [14] and Pakistan [15] have demonstrated a prevalence of cognitive dissonance among its populations, in which there is a significant gap between what is known about the virus as a health threat and what is done to prevent its transmission. Given what is already known about the COVID risk behaviors that college students engage in, it is likely that young adults in the U.S. also experience cognitive dissonance [16], in which their engagement in COVID-19-related risky behavior contradicts their beliefs and desires to prevent transmission of the virus.…”
mentioning
confidence: 99%
“…Research shows that men and those who do not have health risk factors themselves or in their families, those with more education, and those from a higher socioeconomic position are less likely to follow recommended public health guidelines [11e13]. Furthermore, studies of health behaviors in Brazil [14] and Pakistan [15] have demonstrated a prevalence of cognitive dissonance among its populations, in which there is a significant gap between what is known about the virus as a health threat and what is done to prevent its transmission. Given what is already known about the COVID risk behaviors that college students engage in, it is likely that young adults in the U.S. also experience cognitive dissonance [16], in which their engagement in COVID-19-related risky behavior contradicts their beliefs and desires to prevent transmission of the virus.…”
mentioning
confidence: 99%